Synthesis and profiling of antimalarial side-chain modified pyrido[1,2-a]benzimidazoles - Barnard, Linley Nicole (Department of Chemistry, 2018)
The currently available malaria drugs in the market are unsatisfactory in many respects. Shortcomings include costly treatments, toxicity and various side effects. The rapid rise of resistant strains of Plasmodium falciparum, particularly in South-East Asia, has rendered even the most promising treatment regimens ineffective. Therefore, there is an urgent need to explore and develop new antimalarial drugs preferably with novel mechanisms of action, multistage activity, good safety profiles and efficacy at low doses. To address this need, structure activity relationship (SAR) and structure property relationship (SPR) studies were carried out on a novel antimalarial chemotype, namely the pyrido[1,2-a]benzimidazoles (PBI) class of compounds. A frontrunner compound based on the PBI scaffold was previously found to possess potent antiplasmodial activity in vitro [IC₅₀(Pf NF54) = 0.11 μM; IC₅₀(Pf K1) = 0.12 μM] and promising oral efficacy (95% at 4×50 mg/Kg p.o) in the in vivo mouse P. berghei model. However, pharmacokinetic (PK) studies showed oral-limited absorption attributed to poor dissolution or solubility. Thus a series of derivatives was synthesized by making structural modifications to the parent PBI scaffold by distorting the symmetry through introduction of small groups in the C-2 position (Figure i), in an effort to identify derivatives with improved solubility properties, while retaining antiplasmodial activity. The synthesized derivatives displayed good antiplasmodial activity against the chloroquine-sensitive (NF54) strain of P. falciparum and selected compounds against the multi-drug resistant (K1) strain. However, substitutions at the C-2 position resulted in derivatives with improved solubility at the expense of antiplasmodial activity and metabolic stability. In an effort to investigate the factors responsible for improvement in solubility, the dihedral angles of the optimized structures were derived using density functional theory (DFT) calculations (B3LYP/6- 31G*). The calculated dihedral angle of compound 6.4 was compared to the experimentally determined dihedral angle from the single X-ray crystal structure of 6.4. A weak correlation (R² = 0.4) between kinetic solubility and dihedral angle was observed and this suggests that there are many factors that influence solubility and that dihedral angle is just one them.